The deployment of the Malaysian sustainable palm oil standard in the agriculture sector - Mohd Arzaman, Ameer Farhan; Abdul Hamid, Mohd Syaiful Rizal; Razali, Muhamad Amirul; Yasin, Nurul Ibtisyami; Masrom, Nor Ratna; Abdullah Sabri, Nurul Atiqah; Margono, Marlina (Malque Publishing, 2024)
Malaysia's oil palm business is critical to the country's agricultural growth through its contributions to the country's Gross Domestic Product (GDP), foreign exchange, and employment. Oil palm is in high demand because it produces a high yield at a low cost of production. The Malaysian government declared that the Malaysian Sustainable Palm Oil Certification (MSPO) will be necessary by the end of 2020, as a result of greater awareness of environmental and sustainable issues. The objective of this study was to investigate how to deploy MSPO standards in the agriculture sector and to point out the benefit of applying MSPO standards in the agriculture sector. The case study approach and interviews were conducted based on the MSPO Certification, Oil Palm Management Certification and Supply Chain Certification. The findings demonstrated that with the guideline from the standards help to guide the farmers and the small holders to manage the waste, managing fertilizer packaging containers and poison container properly. The MSPO standards bring improvement towards the sale of palm oil and help reduce the problem regarding palm oil. MSPO certification are not only designed to address social and environmental issues but is also designed to demonstrate positive impacts as a result of implementation of better agricultural practices aimed at enhancing efficiency, farm management, improved social development and climate change adaptation.